Pengaruh Live Streaming dan Media Social dalam Meningkatkan Kepercayaan Merek dan Keterlibatan Pelanggan terhadap Keputusan Pembelian Ulang Produk Skincare - Azizah, Nadhifa Najla Nur (Innovative: Journal Of Social Science Research, 2025)
The background of this study is based on the increasing use of social media and live streaming as effective marketing tools in the beauty industry, especially skincare products. The method used is a quantitative approach with data collection techniques through questionnaires distributed to 260 respondents who are active users of social media and have purchased skincare products through live streaming. The data obtained were analyzed using multiple linear regression to test the proposed hypothesis. The results of the study indicate that live streaming has a significant positive effect on brand trust, while social media contributes significantly to increasing customer engagement. In addition, brand trust and customer engagement have been shown to have a positive effect on repurchase decisions for skincare products.